Treatment of atrophic acne scars with combination therapy of chemical reconstruction of skin scars method and fractionated nonablative laser: A retrospective analysis. (16th June 2020) - Bahl, Aanchal; O'Connor, Kelly; Chung, Hye Jin
Abstract: Background: Patients with acne scarring often have several types of acne scars, and combination therapies have demonstrated superior success to single treatment modalities. Chemical reconstruction of skin scars (CROSS) has gained popularity as the treatment for ice‐pick scars and fractionated laser therapy for rolling and boxcar scars. However, no study has looked at combination therapy with CROSS and fractionated nonablative laser for the treatment of atrophic acne scars. Aims: We sought to evaluate the efficacy and safety of combination therapy with CROSS and fractionated nonablative laser for atrophic acne scars. Methods: We conducted a retrospective analysis of patients treated with CROSS followed by fractionated nonablative laser treatment in the same visit for acne scars from 2016 to 2020. Treatment efficacy, defined as the percentage improvement in the appearance of acne scars, was assessed using a 5‐point scale: score 0 (worsening or 0% improvement), 1 (1% ‐ 25%), 2 (26% ‐ 50%), 3 (51%‐75%), and 4 (76%‐100%). Results: Twenty‐five patients (14 females and 11 males, Fitzpatrick Skin Type II –V) were enrolled. The average improvement score was 2.07 after 3 sessions and 2.78 after 5 sessions. All subjects reported satisfaction, while 24% were very satisfied. There were no permanent adverse effects, and only one patient developed a temporary hypertrophic scar. Conclusion: We concluded that combination therapy with CROSS and fractionated nonablative laser in the same visit is an effective and safe treatment option for atrophic acne scars in patients with various skin types, including skin of color.